Postanarchism as a framework for educational authority in higher education - Brogan, Andrew J. (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2026)
When considering anarchist contributions to educational theory and practice, one of the most difficult issues is the presence and use of authority in classroom spaces. The debates focus on how anarchist educators might navigate the tension of a commitment to dismantling assumed authorities while working in environments in which their authority as an educator is constantly reinforced at various levels, be that in the expectations of the students they work with and the institution they work in, the expectations wider society has about their role, and their own expectations and assumptions about what it means to be an educator. This paper explores a possible response for anarchist educators by introducing postanarchist understandings of power and authority to argue for an understanding of authority not as negative per se and thus wholly unjustifiable, but as a particular deployment of a potentially problematic relationship between educators and students, one which can also be enacted differently.
Keywords: Higher Education; Anarchism; Authority